Work from Home, Management, and Technology - Ryo Kambayashi; Atsushi Ohyama (Institute of Labor Economics (IZA), 2025)
We empirically examine whether and how management facilitates Work From Home (WFH) arrangements using data from the 2020 Management and Organizational Practices Survey conducted in Japan (2020 JP MOPS). In this study, we view WFH arrangements as choices made by establishments/firms and analyze the variation in these arrangements across establishments/firms through the lens of managerial heterogeneity. Our empirical investigation reveals the multi-faceted roles management plays in WFH arrangements. First, well-managed establishments tend to adopt advanced digital technologies that support WFH arrangements, positioning management as a mediator in this context. Second, well-managed establishments are more likely than their poorly managed counterparts to implement WFH arrangements independent of technological factors. Performance-based systems with appropriate rewards appear to effectively incentivize remote workers. Finally, WFH arrangements are positively correlated with labor productivity when management scores are high but show no correlation when management scores are low. Thus, management plays a moderating role in the relationship between WFH arrangements and labor productivity. The overall findings from this study suggest that heterogeneity in management among establishments contributes to the variation in WFH arrangements.
Keywords: M54; L25; O33; 330; WFH; structured management; advanced technology